The Effect of Technology Revenue Model and Tax Digitalization on Taxpayer Reporting with Internet Convenience - Parso , Parso (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to evaluate the effect of the Technology Revenue Model and digital taxation on taxpayer reporting by considering the ease of internet factors. The research method uses multiple regression analysis and takes into account moderation by means of interaction methods. The collected data is processed using the Smart PLS Application. Sample from a study of 100 MSMEs Individual Taxpayers who operate or have independent businesses in the Jakarta area. With the result that the Technology Revenue Model and tax digitization do not have a significant influence on taxpayer reporting. However, the ease of the internet has proven to have a significant positive influence on taxpayer reporting. In addition, it was found that the ease of the internet moderated the effect of the Technology Revenue Model significantly positively on the reporting of MSME taxpayers in the Jakarta area. However, the ease of the internet moderates the effect of tax digitalization significantly on the reporting of MSME taxpayers in the Jakarta area.